Probing the 6Li cluster structure with alpha-particle elastic scattering - Urazbekov, B; Denikin, A.S. (Eurasian Journal of Physics and Functional Materials, 2026)
The three-body model a + n + p for 6Li is applied as a probe with elastic scattering of a -particles. Elastic scattering is described within the optical model framework, while the rising of the cross section at the backward scattering angles is treated by means of an approximation of the np transfer mechanism. Both parts of the optical potential are obtained by fitting the depths of the same folding potentials to experimental data. The folding potential, in turn, is based on the three body-wave function of 6Li. Spectroscopic amplitudes for the np cluster are extracted in calculations based on the CRC method. One-step and two-step transfer mechanisms are taken into account for the np transfer mechanism. The calculation results indicate the dominance of the one-step mechanism over the two-step transfer mechanism of the np cluster. © 2022. Eurasian Journal of Physics and Functional Materials.All Rights ReservedRecommended CitationUrazbekov, B. A. and Denikin, A. S. (2022) "Probing the 6Li cluster structure with alpha-particle elastic scattering," Eurasian Journal of Physics and Functional Materials: Vol. 6: No. 2, Article 1.DOI: https://doi.org/10.32523/ejpfm.2022060201